Uchylenie czynności zameldowania na pobyt stały lub czasowy w świetle orzecznictwa sądów administracyjnych - Jurzyński, Maciej (Studia Prawa Publicznego, 2026)
The registration requirement is the basis for keeping population records in Poland. One element concerns the obligation to register at the place of permanent or temporary residence. The legislator decided that the purpose of registration is solely to confirm the fact of the person’s stay in the place where he or she registered. However, in practice, it happens that natural persons report and are registered in a place where they do not actually reside. Such situations are contrary to the purpose of the population register, which is to provide public authorities with information on the place of residence and stay of natural persons. Therefore, using the dogmatic-legal method, the article analyses the issue of the admissibility of annulment the registration procedure for permanent or temporary residence made inconsistently with the actual situation. The relevant provisions of the Population Registration Act and their interpretation in the context of decisions of administrative courts are analyzed, leading to the conclusion that registration is essentially material-technical activity of the municipality. While the legislator has not directly regulated the procedure for revoking a registration activity performed inconsistently with the factual state, the jurisprudence has established a principle for annulling such a defective act at any time. The case law assumes that the annulment of the registration procedure may only take place the form of an administrative decision, i.e. a decision of an authoritative nature, after the municipal authority has conducted administrative proceedings with the participation of all parties and after a detailed explanation of the facts of the case. In order for the registration procedure to be annulled, there must be unequivocal proof that the registration entry regarding the permanent or temporary person’s place of residence is defective.